THE IMPLEMENTATION OF RHETORICAL CANONS IN MATTHEW MCCONAUGHEY’S UVALDE SPEECH - Manurung, Selamat Tumpal (Jurnal Ilmiah Spectral, 2025)
This study investigates Matthew McConaughey’s White House speech concerning the 2022 Robb Elementary School shooting in Uvalde, Texas, analyzing its persuasive strategies through the lens of Cicero’s five canons of rhetoric: Invention, Arrangement, Style, Memory, and Delivery. Employing a qualitative content analysis approach, the research analyze the speech transcript and video to identify artistic tools (ethos, pathos, logos), structural organization, stylistic choices, the speaker’s command of the material, and his physical presentation. Findings indicate the implementation of all five canons. McConaughey’s Invention features pathos through victim narratives, reinforced by his ethos as a Uvalde native and appeals to logos through proposed policy solutions. The speech’s Arrangement effectively utilizes a problem-solution structure, moving from emotional appeals to logical calls for action. Stylistically, the speech employs vivid imagery, repetition, and various rhetorical figures to amplify its message. While not relying on rote memorization, McConaughey’s Memory is evident in his internalization and authentic emotional connection to the content. Finally, his Delivery, characterized by empathetic vocal modulation, strategic pacing, purposeful gestures, and sincere facial expressions, significantly contributed to the message’s impact and authenticity. This research demonstrates the enduring relevance of classical rhetorical principles in contemporary public discourse, particularly in addressing sensitive national tragedies and advocating for policy change, suggesting the potential for further exploration into the long-term impact of such celebrity rhetoric.